Islam in the Modern World: Religion, Ideology and Development - HANAFI, Hassan (Dar Kebaa Bookshop, 2000)
Islam in the Modern World: Religion, Ideology and Development Ideologi Islam Islam Dunia Modern Keagamaan Pengelolaan Islam Modern